Clinical Utility of Cognistat in Multiprofessional Team Evaluations of Patients with Cognitive Impairment in Swedish Primary Care. (23rd March 2014) - Johansson, Maria M.; Kvitting, Anna S.; Wressle, Ewa; Marcusson, Jan
Abstract : Background . Diagnostic evaluations of dementia are often performed in primary health care (PHC). Cognitive evaluation requires validated instruments. Objective . To investigate the diagnostic accuracy and clinical utility of Cognistat in a primary care population. Methods . Participants were recruited from 4 PHC centres; 52 had cognitive symptoms and 29 were presumed cognitively healthy. Participants were tested using the Mini-Mental State Examination (MMSE), the Clock Drawing Test (CDT), and Cognistat. Clinical diagnoses, based on independent neuropsychological examination and a medical consensus discussion in secondary care, were used as criteria for diagnostic accuracy analyses. Results . The sensitivity, specificity, positive predictive value, and negative predictive value were 0.85, 0.79, 0.85, and 0.79, respectively, for Cognistat; 0.59, 0.91, 0.90, and 0.61 for MMSE; 0.26, 0.88, 0.75, and 0.46 for CDT; 0.70, 0.79, 0.82, and 0.65 for MMSE and CDT combined. The area under the receiver operating characteristic curve was 0.82 for Cognistat, 0.75 for MMSE, 0.57 for CDT, and 0.74 for MMSE and CDT combined. Conclusions . The diagnostic accuracy and clinical utility of Cognistat was better than the other tests alone or combined. Cognistat is well adapted for cognitive evaluations in PHC and can help the general practitioner to decide which patients should be referred to secondary care.